High Prevalence of Antimicrobial Resistance and Integron Gene Cassettes in Multi-Drug-Resistant Klebsiella pneumoniae Isolates From Captive Giant Pandas (Ailuropoda melanoleuca) - Yan, Xia; Su, Xiaoyan; Ren, Zhihua; Fan, Xueyang; Li, Yunli; Yue, Chanjuan; Yang, Mei; Deng, Huidan; Deng, Youtian; Xu, Zhiwen; Zhang, Dongsheng; Li, Lin; et al. (Frontiers in Microbiology, 2022)
Multi-drug-resistant (MDR) Klebsiella pneumoniae (K. pneumoniae) is increasingly being reported with corresponding increase in morbidity and mortality all over the world. However, limited information is available concerning MDR K. pneumoniae in giant pandas. The objective of this study was to grasp the drug resistance profile of MDR K. pneumoniae isolated from giant pandas. A total of 182 K. pneumoniae isolates were collected from fresh feces of 94 captive giant pandas of different ages and sex. We performed a standard disk diffusion antimicrobial susceptibility test with 182 K. pneumoniae isolates and further evaluated the mobile genetic elements (MGEs) and integron gene cassettes of MDR strains. Antimicrobial susceptibility testing results demonstrated that a total of 30 (16.5%, n = 30/182) K. pneumoniae isolates showed multiple drug resistances. Thirty MDR K. pneumoniae isolates were mainly resistant to AMX (100.0%), DOX (86.7%), CHL (60.0%), SXT (60.0%) and TMP (56.7%). Fifty different types of ARGs were found which included 671 ARGs in 30 MDR isolates, the top ten resistance genes were: vanTC-02, aacC, blaCTX-M-04, blaSHV-01, blaSHV-02, ampC-04, blaOXY, tetD, blaTEM and tetA-02. Thirteen mobile genetic elements were detected, of which IS26 (96.67%, n = 29) had the highest frequency. All isolates were negative for the traA, traF, tnsA, IS1133, ISpa7, ISkpn6, intI2 and intI3 genes. Moreover, a further investigation of integrons revealed that the emergence of class 1 integrons were in 96.67% of the isolates, while class 2 and class 3 integrons were not screened. Two types of specific gene cassettes (dfrA12+orfF+aadA2 and dfrA12+orfF) were identified in class 1 integrons. Our results illustrate that effective surveillance and strict biosecurity strategies should be taken to prevent the spread of MDR bacteria, and monitor the emergence of MGEs integrons.